Mini-review: the utility of macroalgae in abalone diets and their role in heat resilience - Murni, Ida Ayu Amarilia Dewi; Supono, Supono (Jurnal Akuakultur Indonesia, 2025)
Abalone aquaculture production is predicted to continue to increase. Nutrition and health aspect are becoming two major issues that can impede the development and economic sustainability of abalone aquaculture industries. Feeding fresh macroalgae to abalone has supply inconsistency and biosecurity issues in the culture system. The utilization of commercially formulated diets could improve abalone growth rates. However, in general, the health condition of abalone which has been fed commercially formulated feeds was lower than abalone fed fresh macroalgae diets. An abalone diet should not only need to sustain a high growth rate but also promote optimal health. The use of dried macroalgae meal as a dietary ingredient in formulated diets for abalone could potentially increase growth rate, reduce feed costs and gain the health and immunity benefits of macroalgae. This review aims to improve understanding of the potential benefits of using fresh and dried marine macroalgae as feed ingredients to provide nutritional and health improvements for abalone. Keywords: abalone, aquaculture, health, macroalgae, nutritional requirement ABSTRAK Produksi budidaya abalon diperkirakan terus meningkat. Aspek gizi dan kesehatan menjadi dua isu besar yang dapat menghambat perkembangan dan keberlanjutan ekonomi industri budidaya abalon. Pemberian pakan makroalga segar ke abalon memiliki permasalahan pada ketersediaan pasokan yang tidak konsisten dan biosekuriti dalam sistem budidaya. Pemanfaatan pakan komersial dapat meningkatkan laju pertumbuhan abalon. Namun secara umum, kondisi kesehatan abalon yang diberikan pakan formula komersial lebih rendah dibandingkan dengan abalone yang diberikan pakan makroalga segar. Pakan abalon sebaiknya tidak hanya perlu meningkatkan pertumbuhan tetapi juga meningkatkan kesehatan yang optimal. Penggunaan tepung makroalga kering sebagai bahan makanan dalam formulasi pakan abalon berpotensi meningkatkan laju pertumbuhan, mengurangi biaya pakan dan mendapatkan manfaat kesehatan dan kekebalan dari makroalga. Kajian ini bertujuan untuk meningkatkan pemahaman tentang potensi manfaat penggunaan makroalga laut segar dan kering sebagai bahan pakan untuk memberikan peningkatan nutrisi dan kesehatan abalon. Kata kunci: abalon, budidaya, kebutuhan nutrisi, kesehatan, makroalga